2002
DOI: 10.1089/08977150252932361
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Profile of Cortical Perfusion and Microcirculation after Controlled Cortical Impact Injury in Rats

Abstract: Impaired cerebral perfusion contributes to evolving posttraumatic tissue damage. Spontaneous reversibility of reduced perfusion within the first days after injury could make a persisting impact on secondary tissue damage less likely and needs to be considered for possible therapeutic approaches. The present study was designed to characterize the temporal profile and impact of trauma severity on cortical perfusion and microcirculation during the first 48 h after controlled cortical impact injury (CCI). In 10 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 46 publications
4
51
0
Order By: Relevance
“…Interpretation of decreased CBV as a hypoperfusion immediately after TBI seems reasonable, because the CBV and CBF have been shown to be linked in experimental studies of TBI in acute phase (Prat et al, 1997;Thomale et al, 2002). Furthermore, we observed CBV drop during the first hours after head trauma, at the time when decrease in perfusion (CBF) has been well documented by several research groups (Prat et al, 1997;Thomale et al, 2002;Ginsberg et al, 1997;Bryan et al, 1995). Similarly, we attributed the increased CBV in the hippocampus in subacute phase to increased CBF.…”
Section: Methodological Considerationssupporting
confidence: 78%
See 2 more Smart Citations
“…Interpretation of decreased CBV as a hypoperfusion immediately after TBI seems reasonable, because the CBV and CBF have been shown to be linked in experimental studies of TBI in acute phase (Prat et al, 1997;Thomale et al, 2002). Furthermore, we observed CBV drop during the first hours after head trauma, at the time when decrease in perfusion (CBF) has been well documented by several research groups (Prat et al, 1997;Thomale et al, 2002;Ginsberg et al, 1997;Bryan et al, 1995). Similarly, we attributed the increased CBV in the hippocampus in subacute phase to increased CBF.…”
Section: Methodological Considerationssupporting
confidence: 78%
“…Marked decrease in CBV and CBF has been found 3 to 4 h after injury in the rat model of closed head injury (Prat et al, 1997;Thomale et al, 2002). Local CBF has been found to decrease 15 mins after injury and remain decreased up to 4 h in lateral fluid percussion rat models (Ginsberg et al, 1997) and similar patter of CBF has been found in humans Kelly et al, 1996Kelly et al, , 1997.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Thomale et al showed that the acute hypoperfusion after TBI is due to vasoconstriction (Thomale et al 2002). This study also found hyperemia occurring between 24 and 48 h after TBI in the controlled cortical impact model using LDF.…”
Section: Laser Doppler Flowsupporting
confidence: 74%
“…Ultrastructural alterations in the lumen and wall of sensorimotor cortical microvessels, including endothelial cell distortion and luminal collapse, were seen between 1 and 48 h after trauma. Smooth muscle in the wall of reacting microvessels showed evidence of increased contractility that coincided temporally with the decreased perfusion of cortical CBF.Thomale et al showed that the acute hypoperfusion after TBI is due to vasoconstriction (Thomale et al 2002). This study also found hyperemia occurring between 24 and 48 h after TBI in the controlled cortical impact model using LDF.…”
supporting
confidence: 62%